The future of the industrial AI edge is cellular - Foukas, Xenofon; Radunovic, Bozidar (HotMobile, 2025)
Ensuring reliable and high-bandwidth wireless connectivity and local processing at the edge are crucial enablers for emerging industrial AI applications. In this work, we argue that the recent trends in cellular networking make the technology the ideal connectivity solution for these applications, due to its virtualization and support for open APIs. We foresee the emergence of a converged industrial AI edge encompassing both compute and connectivity, in which application developers leverage the API to implement advanced functionalities. We demonstrate the usefulness of this approach through a case study evaluated on an enterprise-grade 5G testbed deployed in our lab.